The Ancient World : From the Earliest Times to 800 A.D. - Betten, Francis S. (Allyn and Bacon)
Contiene: 1. El Oriente; 2. Los griegos; 3. El mundo greco-oriental; 4. Roma; 5. El imperio romano; 6. Romano-teutónico europeo.